2012
DOI: 10.1080/01635581.2012.689916
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Vitamins D and A and Calcium and Risk of Non-Hodgkin Lymphoma: San Francisco Bay Area Population-Based Case-Control Study

Abstract: Several nutrients identified as potentially cancer protective have been inconsistently associated with non-Hodgkin lymphoma (NHL) risk. Dietary history data, including use of vitamin supplements, were collected using a semi-quantitative food frequency questionnaire administered during in-person interviews with 4,133 participants (2052 cases, 2081 controls) in a San Francisco Bay Area population-based case-control. Data were used to determine the association of intake levels of vitamins D, A and calcium with ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
(96 reference statements)
0
7
1
Order By: Relevance
“…Such an investigation, however, is made difficult by the relatively small sample sizes available for analysis. For instance, Polesel et al (41) showed an inverse association between dietary intake of vitamin D and the risk of FL (n = 31), in contradiction with our analysis, whereas Bahar et al documented an increased risk of DLBCL with higher dietary vitamin D in agreement with our data (42).…”
contrasting
confidence: 56%
“…Such an investigation, however, is made difficult by the relatively small sample sizes available for analysis. For instance, Polesel et al (41) showed an inverse association between dietary intake of vitamin D and the risk of FL (n = 31), in contradiction with our analysis, whereas Bahar et al documented an increased risk of DLBCL with higher dietary vitamin D in agreement with our data (42).…”
contrasting
confidence: 56%
“…With the exception of a few studies that found positive associations with consumption of processed meat and poultry, 4 total carbohydrate 8 or fat (in women) 11 intake, and inverse associations with isoflavones consumption, 10 generally large prospective studies found no associations between a wide range of dietary factors and CLL. By contrast, case-control studies have yielded contradictory results for meat, 13 , 14 , 16 , 24 , 25 dairy products, 13 17 fish 15 , 18 or vegetables and fruit 14 , 16 , 19 , 22 , 23 , 25 intake.…”
Section: Discussionmentioning
confidence: 98%
“…On the one hand, prospective studies looking for associations between CLL and nutrients or individual food items have found positive associations with poultry and processed meat [44], total fat [45] or carbohydrate [46] intake (in women), and inverse associations with the consumption of isoflavones [47]. On the other hand, case-control studies have found inconsistent evidence for the associations between CLL and dairy products, fish, meat, fruits and vegetables [6][7][8][9][10][11][12][13][14][15][16][17]. Due to this, in recent decades, nutritional epidemiology has transitioned toward studying dietary patterns in order to assess their risk of disease [43].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, exposure to UV radiation and atopic conditions were inversely associated with CLL [5]. Regarding diet, case-control studies have obtained controversial results for individual nutrients such as meat, dairy products and vegetables [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%